How many captains for a ship on electoral drift? Limiting the number of leadership candidates in the Flemish Christian-democratic party (CD&V) - Luypaert, Jasmien; Lingier, Leen; Bouteca, Nicolas; Vandeleene, Audrey; Wauters, Bram (Frontiers in Political Science, 2022)
Many Western parties have opened up the process of leadership selection to party members under the noble premises to democratize the party. Yet, this might just be window-dressing as party leadership selection is often a coronation rather than an open contest. We argue that the preparation phase preceding the actual election phase is crucial in understanding the balance between the impact of party members and the steering of the party elite. This study compares the preparation phase of two leadership contests after losing elections in one party, the Flemish Christian-democratic party in Belgium: one with a single candidate and one with an exceptionally high number of candidates. Our analysis, based on 22 in-depth elite interviews, demonstrates that leadership elections are influenced by a cluster of different influencing actors, but in particular by what we label the “last person standing” whose candidacy is identified as the most effective mechanism to influence the nomination process. Other (slightly less effective) influencing mechanisms include encouragements, discouragements and the diffusion of an ideal profile for the future party leader.